Effect of Rumen Undegraded Protein Level on Nutrient Digestibility and Rumen Fermentation Parameters of Dairy Cow - Widyobroto B. P.; S. P. S. Budhi; A. Agus; B. Santosa (Faculty of Animal Science, Universitas Gadjah Mada, 2002)
Artikel dalam bentuk PDF